Visual fields, visual acuity, and driving performance in patients with pituitary adenoma before and after surgery - Schneider, Evelin; Gramer, Gwendolyn; Schargus, Marc; Gramer, Eugen (Neuro-ophthalmology, 2011)
We evaluated the prognosis of visual fields, visual acuity, and fitness to drive and the phenomenon of statokinetic dissociation in patients with pituitary adenoma who undergo surgery. In patients with pituitary adenoma, visual requirements for on road driving performance and the role of statokinetic dissociation have not been evaluated previously. Twenty-eight patients (56 eyes) with pituitary adenoma were included in the study over a period of 5 years and consecutively examined before and after surgery by the same ophthalmologist. Preoperatively, out of 56 eyes, we found visual field defects in 31 eyes (55%) and visual acuity impairment in 23 eyes (41%). Postoperatively, 24 out of 28 patients (86%) met the legal binocular visual requirements for driving a car in Germany. In 31 eyes with visual field defects (VFD), 64% of VF improved after surgery. Visual acuity impairment was reduced postoperatively in 75%, 10% remained unchanged, and 15% deteriorated, but 2/3 of these improved after second surgical intervention. All 28 patients were legally fit to drive postoperatively. Statokinetic dissociation was evaluated in 22 eyes with reliable static and kinetic double examination, performed on the same day. In 16 eyes (73%), computerised static perimetry (Octopus perimetry, central 30°, full threshold strategy) showed considerably more severe VFD than kinetic perimetry (i.e., statokinetic dissociation was ascertained). From this study we conclude that 60% of patients with pituitary adenoma can hope for significant improvement of visual function (64% in VF, 75% in visual acuity) after surgery, and driving permission can often be regained. Due to statokinetic dissociation, kinetic perimetry should be complemented by automated static perimetry.